SASBat audio steganography using Bat-Algorithm-based OLSB substitution with PGP encryption - Viñas, Vina T.; Ultra, John D. (2015)
Through the years, digital multimedia applications have rapidly developed. Alongside this, secure data transmission has become the main issue in data communication system so several data hiding techniques have been developed to ensure the security of a data transfer. Audio steganography, which is a technique used to transmit hidden information by modifying an audio signal in an imperceptible manner, is one of the methods used today to ensure the security of data transfer between the sender and the recipient.
In this study, we present a new approach in embedding a message in an audio file. The message will be encrypted through PGP and the Bat-Algorithm-based OLSB substitution technique will be used in embedding the encrypted message bits into k LSB layers reducing noise distortions and increasing the robustness of the audio file with the hidden message. The performance evaluation of the embedded audio file is done by calculating the Mean Square Error (MSE) and comparison of the Peak-Signal-to-Noise-Ratio (PSNR) values. The proposed method was tested by varying the bat algorithm parameters (bat population, number of cycles, maximum loudness, and maximum pulse rate),and steganographic parameters (cover audio, secret data, and k LSBs). The results for each experimental setups showed that the proposed approach generated stego audios with high PSNR values and low MSEs. Also, the resulting stego audio with secret data is close to imperceptibility and through PGP, better security and confidentiality is provided to the secret data.
Undergraduate thesis (B.S. in Computer Science)--University of the Philippines, Tacloban.
Keywords: Bat Algorithm; Audio steganography